Contacts with primary and secondary healthcare prior to suicide: case–control whole-population-based study using person-level linked routine data in Wales, UK, 2000–2017. (December 2020) - John, Ann; DelPozo-Banos, Marcos; Gunnell, David; Dennis, Michael; Scourfield, Jonathan; Ford, David V.; Kapur, Nav; Lloyd, Keith
Abstract : Background: Longitudinal studies of patterns of healthcare contacts in those who die by suicide to identify those at risk are scarce. Aims: To examine type and timing of healthcare contacts in those who die by suicide. Method: A population-based electronic case–control study of all who died by suicide in Wales, 2001–2017, linking individuals' electronic healthcare records from general practices, emergency departments and hospitals. We used conditional logistic regression to calculate odds ratios, adjusted for deprivation. We performed a retrospective continuous longitudinal analysis comparing cases' and controls' contacts with health services. Results: We matched 5130 cases with 25 650 controls (5 per case). A representative cohort of 1721 cases (8605 controls) were eligible for the fully linked analysis. In the week before their death, 31.4% of cases and 15.6% of controls contacted health services. The last point of contact was most commonly associated with mental health and most often occurred in general practices. In the month before their death, 16.6 and 13.0% of cases had an emergency department contact and a hospital admission respectively, compared with 5.5 and 4.2% of controls. At any week in the year before their death, cases were more likely to contact healthcare services than controls. Self-harm, mental health and substance misuse contacts were strongly linked with suicide risk, more so when they occurred in emergency departments or as emergency admissions. Conclusions: Help-seeking occurs in those at risk of suicide and escalates in the weeks before their death. There is an opportunity to identify and intervene through these contacts.